Comparative evaluation of digital radiography, electronic apex locator and simultaneous working length determination on postoperative pain after root canal treatment: a randomized clinical trial - Boris Saha; Sharique Alam; Daiasharailang Lyngdoh; Surendra Kumar Mishra (European Oral Research)
Purpose: The study aimed to compare postoperative pain after root canal preparation using three different methods of working length determination.Materials and Method: 60 patients diagnosed with symptomatic irreversible pulpitis were randomly divided into three groups based on the method of working length (WL) determination. Group 1: digital radiograph (DRG), Group 2: electronic apex locator (EAL), Group 3: the simultaneous working length control (SLC) method using an endomotor with an integrated apex locator. The root canal treatments were completed in a single visit, and patients were asked to record their pain response using the Visual Analog Scale (VAS) at 6, 24, 48, and 72 hours postoperatively.Results: Group 1 (DRG) recorded the highest postoperative pain score, while the lowest was recorded by Group 3 (SLC). There was a statistically significant difference in the VAS pain scores between DRG and SLC (p<0.05) at 6-, 24- and 48-hour intervals.Conclusion: Within the limitations of this study, it can be concluded that the SLC can be a helpful working length determination technique to reduce postoperative pain.